A pilot study of the effect of Kinesiology tape on knee proprioception after physical activity in healthy women. Issue 6 (November 2015) - Hosp, Simona; Bottoni, Giuliamarta; Heinrich, Dieter; Kofler, Philipp; Hasler, Michael; Nachbauer, Werner
Abstract: Objectives: Kinesiology tape has gained significant popularity in recent years and is widely used as an adjunct for treatment and prevention of musculoskeletal injuries. However, evidence regarding its influence on knee proprioception is scarce. The purpose of this study was to evaluate the effect of Kinesiology tape on knee proprioception after physical activity in healthy women. It was hypothesized that Kinesiology tape enhances knee proprioception. Design: Longitudinal analysis, pretest–posttest design. Methods: Twelve young women with healthy knees were tested for knee proprioception without the use of Kinesiology tape and wearing Kinesiology tape at the knee. The joint position sense was measured at the start and after a 30-min uphill walking protocol on a treadmill. Outcome was the knee angle deviation. Results: No significant difference of proprioceptive performance between the application with Kinesiology tape and without Kinesiology tape was found after uphill walking ( p  > 0.05). However, when the participants' results for knee angle deviation were graded into good (<6.1°) and poor (>6.1°), Kinesiology tape significantly enhanced those with poor proprioceptive ability after uphill walking, compared to the untaped knee ( p  = 0.002). Conclusions: This study has shown that the application of Kinesiology tape did not improve knee proprioception in a group of healthy young women. However, it also has demonstrated that Kinesiology tape provided significant proprioceptive enhancement at the knee joint after uphill walking in healthy women with poor proprioceptive ability. This may support its use in sports medicine for preventing knee injuries.